The investigations book : a resource book for teachers of mathematics - Holding, John. (United Kingdom : Cambridge University Press, 1991)
Since the introduction of the National Curriculum, the interest in using mathematical investigations in the classroom at both primary and secondary level has grown. This text gives a rationale for investigative work within mathematics lessons and contains 40 investigations.
Includes index.
Keywords: Mathematics -- Study and teaching (Primary).; Mathematics -- Study and teaching (Secondary).